Concealed penile duplication - Presenting late - K Abhishek Reddy; Vinay Chandrashekar; Sanjay Rao; Ashley D'cruz (Wolters Kluwer Medknow Publications, 2022)
We report a case of concealed penile duplication without many symptoms and normally looking external genitalia in a 10-year-old boy. He was evaluated with appropriate imaging and had successful surgical reconstruction of his genitalia with good cosmesis and functional outcome.